Detection of Second Primary Malignancies of the Esophagus and Hypophraynx in Oral Squamous Cell Carcinoma Patients. Issue 4 (9th August 2018) - Matsui, Toshihiro; Okada, Takuya; Kawada, Kenro; Okuda, Masahumi; Ogo, Taichi; Nakajima, Yutaka; Kume, Yuichiro; Ryotokuji, Tairo; Hoshino, Akihiro; Tokairin, Yutaka; Michi, Yasuyuki; Harada, Hiroyuki; et al.
Abstract : Objective: To assess the usefulness of modified esophagogastroduodenoscopy (EGD) for the detection of second primary malignancies of the esophagus or hypopharynx in patients with oral squamous cell carcinoma and determine the association between the oral lesion subsite and esophageal or hypopharyngeal lesion occurrence. Study Design: Retrospective review. Methods: In total, 166 patients with oral squamous cell carcinoma without any established symptoms of esophageal or hypopharyngeal squamous cell carcinoma underwent modified EGD based on the Valsalva maneuver and U‐turn method, image‐enhanced endoscopy, and chromoendoscopy using Lugol's iodine for diagnosis. All suspected lesions were biopsied to determine the clinical stages and duplication rates. Odds ratios for the occurrence of duplicate lesions according to the oral lesion subsite were determined. Results: In total, 37 esophageal and 16 hypopharyngeal lesions were detected. According to the Union for International Cancer Control/American Joint Committee on Cancer classification (2009), 75.7% and 5.4% esophageal lesions were classified as stage IA and IB, respectively, and 50% and 18.8% hypopharyngeal lesions as stage II and stage I, respectively. Approximately 59.1% and 50% esophageal and hypopharyngeal lesions, respectively, were successfully treated by endoscopic resection. Oral lesions involving the floor of the mouth were more frequently accompanied by second primary malignancies of the esophagus or hypopharynx. Conclusions: Modified EGD is an effective noninvasive technique for early diagnosis and treatment of second primary malignancies of the esophagus and hypopharynx in patients with oral squamous cell carcinoma. In particular, patients with floor of the mouth lesions need close monitoring for hypopharyngeal and esophageal lesions. Level of Evidence: 3b.